2021
DOI: 10.1002/adma.202005907
|View full text |Cite
|
Sign up to set email alerts
|

Atomic‐Layer‐Deposition‐Based 2D Transition Metal Chalcogenides: Synthesis, Modulation, and Applications

Abstract: V, Fe, Co, and Ni chalcogenides exhibit diverse stoichiometric phases with different electrical properties. [28][29][30] For example, TiS 3 is a semiconductor, while TiS 2 exhibits metallic properties. [30,31] Owing to their electrical conductivity, metallic TMCs can be used for energy conversion (including the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER)) and energy storage (Li-ion batteries (LIBs), Na-ion batteries (NIBs), and supercapacitors). [29,32] Industrially compatible synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 200 publications
(357 reference statements)
0
37
0
Order By: Relevance
“…As for the chalcogen precursors, the reported chalcogen sources include hydrogen sulfide (H 2 S) and di- tert -butyl disulfide (TBDS) for sulfur and diethyldiselenide (DEDSe) for selenium (Figure ). The gaseous H 2 S, owing to its good ALD reactivity, has been prevalently used in the ALD of metal sulfides, for not only the above three metals but also many others. , H 2 S resembles H 2 O in molecular structure, but owing to its weaker S–H bond, H 2 S is a stronger Brønsted–Lowry acid than H 2 O. Therefore, H 2 S is presumably more reactive than H 2 O toward proton-mediated ligand-exchange reactions, which are considered as the governing mechanisms in many ALD processes.…”
Section: Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the chalcogen precursors, the reported chalcogen sources include hydrogen sulfide (H 2 S) and di- tert -butyl disulfide (TBDS) for sulfur and diethyldiselenide (DEDSe) for selenium (Figure ). The gaseous H 2 S, owing to its good ALD reactivity, has been prevalently used in the ALD of metal sulfides, for not only the above three metals but also many others. , H 2 S resembles H 2 O in molecular structure, but owing to its weaker S–H bond, H 2 S is a stronger Brønsted–Lowry acid than H 2 O. Therefore, H 2 S is presumably more reactive than H 2 O toward proton-mediated ligand-exchange reactions, which are considered as the governing mechanisms in many ALD processes.…”
Section: Precursorsmentioning
confidence: 99%
“…ALD of metal chalcogenides can be dated back to the 1970s, when the first ZnS ALD process was reported using elemental Zn and S as precursors . However, in the following years, the development of chalcogenide ALD was relatively scarce, as compared to oxide ALD, until the past decade, when there has been a great resurgent interest in the ALD of metal chalcogenides. Many new ALD processes have been recently developed for metal chalcogenides, and their applications have also been extensively explored. Iron, cobalt, and nickel chalcogenides are among those materials that have been only recently realized by ALD. , Iron, cobalt, and nickel are neighboring elements in the periodic table, and they are similar in chemical properties but different with a progressive increase in the number of 3d electrons. The chalcogenides of iron, cobalt, and nickel often form similar crystal structures, which therefore offer a desirable platform for electronic structure engineering by alloying these elements.…”
Section: Introductionmentioning
confidence: 99%
“…In the conventional ALD of TMDCs, however, the grown TMDC films are amorphous owing to the low deposition temperature and are subsequently annealed at a higher temperature for crystallization. [14][15][16][17][18] In these cases, the grain size is restricted to the range of several nanometers to a few tens of nanometers. Some studies have reported the ALD growth of crystallized TMDC films.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic layer deposition and atomic layer etching (ALE) techniques in principle meet this demand . The former is a well-established technique and has been developed for bottom-up growth of conformal thin films. , The latter can provide nanosheets by means of thinning existing 2D materials layer by layer using sequential, self-limiting reactions. , The plasma ALE method, one of the ALE methods, has recently attracted the attention of this research field because of its good selectivity, scalability, and short processing duration. , A low-temperature gas plasma commonly contains several highly reactive species such as ions, free radicals, electrons, and so on . These species rapidly initiate chemical reactions that are inactive under common conditions.…”
Section: Introductionmentioning
confidence: 99%
“…14 The former is a well-established technique and has been developed for bottomup growth of conformal thin films. 15,16 The latter can provide nanosheets by means of thinning existing 2D materials layer by layer using sequential, self-limiting reactions. 17,18 The plasma ALE method, one of the ALE methods, has recently attracted the attention of this research field because of its good selectivity, scalability, and short processing duration.…”
Section: ■ Introductionmentioning
confidence: 99%